2017
DOI: 10.4236/ojg.2017.76052
|View full text |Cite
|
Sign up to set email alerts
|

Soil Salinity and Alkalinity Map Preparation Based on Spatial Analysis of GIS (Case Study: Tabriz Plain)

Abstract: Better management of agricultural fields is related to valuable information which can derived from soil salinity and alkalinity maps. These maps are considered as one of the most important factors which restrict plant growth as well as decline crops yield. The objective of this research was preparing of soil salinity and alkalinity maps in Tabriz plain over 50,000 hectares based on different techniques of spatial analysis in GIS software. For this mean, study area was divided in 1500 × 1500 m 2 grid cells. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…In many cases, the Kriging method proved to be the best estimator, i.e., ordinary Kriging (OK), while inverse distance weighting (IDW) or splines were considered appropriate methods in other cases [33][34][35][36][37]. The interpolation based on inverse distance weight (IDW) is an accurate method for mapping saline soils, according to Farajnia and Yarahmadi (2017) [38]. In addition, many studies using soil-landscape analysis have shown that it can be a very good indicator of the distribution of soil properties in space [39].…”
Section: Introductionmentioning
confidence: 99%
“…In many cases, the Kriging method proved to be the best estimator, i.e., ordinary Kriging (OK), while inverse distance weighting (IDW) or splines were considered appropriate methods in other cases [33][34][35][36][37]. The interpolation based on inverse distance weight (IDW) is an accurate method for mapping saline soils, according to Farajnia and Yarahmadi (2017) [38]. In addition, many studies using soil-landscape analysis have shown that it can be a very good indicator of the distribution of soil properties in space [39].…”
Section: Introductionmentioning
confidence: 99%